Proceedings of the 21st ACM Conference on Economics and Computation 2020
DOI: 10.1145/3391403.3399491
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Learning in Strategic Queuing Systems

Abstract: Bounding the price of anarchy, which quantifies the damage to social welfare due to selfish behavior of the participants, has been an important area of research in algorithmic game theory. In this paper, we study this phenomenon in the context of a game modeling queuing systems: routers compete for servers, where packets that do not get service will be resent at future rounds, resulting in a system where the number of packets at each round depends on the success of the routers in the previous rounds. We model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(75 citation statements)
references
References 20 publications
1
72
2
Order By: Relevance
“…The main result of this paper is to show that with patience by the queues, a factor of −1 ≈ 1.58 extra server capacity over what is needed in the centralized setting suffices to guarantee the stability of the system despite selfishness. This is in contrast to the main result of [5], where it is shown that if queues use no-regret learning, the system needs a factor of 2 extra server capacity. In this setting, the no-regret property implies that queues send to queues with the highest empirical success rates, without accounting for how alternate choices affect these rates.…”
Section: Overview Of Results and Techniquescontrasting
confidence: 79%
See 4 more Smart Citations
“…The main result of this paper is to show that with patience by the queues, a factor of −1 ≈ 1.58 extra server capacity over what is needed in the centralized setting suffices to guarantee the stability of the system despite selfishness. This is in contrast to the main result of [5], where it is shown that if queues use no-regret learning, the system needs a factor of 2 extra server capacity. In this setting, the no-regret property implies that queues send to queues with the highest empirical success rates, without accounting for how alternate choices affect these rates.…”
Section: Overview Of Results and Techniquescontrasting
confidence: 79%
“…Recall that our goal is to ensure stability in any Nash equilibrium, assuming some relationship on the service rates to the arrival rates. Our main result shows that the correct constant of system slack is −1 ≈ 1.58, beating the best achievable constant of 2 in the no-regret setting of [5]: Theorem 1.3 (Main, Corollary 5.2, informal). If the service capacity is large enough so that the system would remain feasible when centrally managed even if capacities are scaled down by −1 , then in every equilibrium of this game, all queues are stable.…”
Section: Overview Of Results and Techniquesmentioning
confidence: 78%
See 3 more Smart Citations